Household Economic Welfare During the Rise of Mobile Phone Expansion in Indonesia - Catra Evan Ramadhani (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2023)
The proliferation of mobile phones in developing countries has significant implications for those countries. Although numerous studies have examined the various advantages of mobile phone use, the relationship between mobile phone access and the economic welfare of households has received comparatively little attention. This paper examines the effects of mobile phone on household expenditures in 2007 and 2014 utilising the Indonesian Family Life Survey (IFLS) combined with Potential Village Survey (PODES). Ordinary Least Square (OLS), Endogenous Treatment Regression (ETR), quantile regression, and two-way fixed effect estimations are used to identify the homogeneous and heterogeneous effects of mobile phone use. According to the estimated results, mobile phone access and signal quality significantly increases household expenditure. According to the results of quantile regression, mobile phone access has the greatest effect on the upper expenditure distributions. It is highlighting the importance of promoting a policy that increases mobile phone and the supporting infrastructure on the lower expenditure distributions.